Differentiated Instruction and Its Implementation in Teaching of Recount Texts: A Case of Applying Genre-Based Approach - Sinta Fatimah; Umi Tursini; Siti Mafulah (EDUJ : English Education Journal, 2024)
Differentiated Instruction is an approach to teaching that considers the diverse learning needs, interests, and abilities of students. In contrast, the genre approach is a pedagogical method focused on teaching writing through the exploration and production of various genres. The objectives of this study are to investigate the implementation of a genre-based approach in teaching recount texts within a differentiated instruction framework, and to assess the impact of this approach on students’ learning outcomes and engagement. This research employs a qualitative method, which is a process of inquiry aimed at understanding human behaviors by creating complex, holistic pictures of the social and cultural contexts in which such behaviors occur. The data instruments include document analysis, observations, and interviews. Participants in this research consist of a teacher and students from SMP Al Azhar Pagelaran Malang. Data analysis follows an interactive model technique, which involves several stages: data reduction, data display, conclusion drawing, and triangulation. The result, teacher conducted an assessment to identify the students' needs. Subsequently, they implemented genre-based approach to make learning recount texts more engaging, allowing students to circulate and exchange information with different groups. From the interview data, it was evident that students enjoyed learning through differentiated instruction. With various learning styles accommodated, students felt confident in their understanding of the material presented in each lesson.